A new interactive computer simulation system for violence risk assessment of mentally disordered violent offenders. (7th January 2013) - Arborelius, Lotta; Fors, Uno; Svensson, Anna‐Karin; Sygel, Kristina; Kristiansson, Marianne
ABSTRACT Background Assessment of risk of future violence has developed from reliance on static indicators towards a more dynamic approach. In the latter context, however, the offender is seldom confronted with real life situations. Aims The aim of this study is to evaluate a computer‐based system – Reactions on Display, which presents human interactions based on real‐life situations – for its effectiveness in distinguishing between potentially violent offenders with mental disorder and a healthy comparison group. Methods Male offenders with autism spectrum disorders or psychosis were recruited from specialist forensic psychiatric units in Sweden and healthy participants from the local communities. Each consenting participant was presented with film clips of a man in neutral and violent situations, which at critical moments stopped the story to ask him to predict the thoughts, feelings and actions of the actor. Results Offender patients, irrespective of diagnosis, detected fewer emotional reactions in the actor in the non‐violent sequence compared with controls. When asked to choose one of four violent actions, the offender patients chose more violent actions than did the controls. They also reported fewer physical reactions in the actors when actors were being violent. There were also some examples of incongruent or deviant responses by some individual patients. Conclusions and implications for practice The use of interactive computer simulation techniques is not only generally acceptable to offender patients, but it also helps to differentiate their current response style to particular circumstances from that of healthy controls in a way that does not rely on their verbal abilities and may tap more effectively into their emotional reactions than standard verbal questions and answer approaches. This may pave the way for Reactions on Display providing a useful complement to traditional risk assessment, and a training route with respect to learning more empathic responding, thus having a role in aiding risk management. Copyright © 2013 John Wiley & Sons, Ltd.